2019
DOI: 10.1111/aphw.12178
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well‐Being and Health Behaviors in 2.5 Million Americans

Abstract: Background Happiness and health behavior are positively related, but most existing research does not distinguish between conceptually and empirically distinct components of subjective well‐being—satisfaction with life, positive affect, and negative affect. Method We assessed the associations of each component of subjective well‐being and health behavior, such as exercising and not smoking, in a broad, representative sample of nearly 2.5 million respondents from the USA in the Gallup Daily Poll. Results We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 38 publications
3
33
0
5
Order By: Relevance
“…However, our finding that frequent gambling does not have a significant relationship with exercise is inconsistent with Håkansson et al [86], who found a positive association between problem gambling and physical activity. Among the behavioral variables, our finding on the positive association of happiness level with regular exercise is consistent with other studies [87][88][89][90]. Intuitively, people with a high level of happiness are more likely to have energy and feel less fatigue than people with depression or a low level of happiness.…”
Section: Discussionsupporting
confidence: 91%
“…However, our finding that frequent gambling does not have a significant relationship with exercise is inconsistent with Håkansson et al [86], who found a positive association between problem gambling and physical activity. Among the behavioral variables, our finding on the positive association of happiness level with regular exercise is consistent with other studies [87][88][89][90]. Intuitively, people with a high level of happiness are more likely to have energy and feel less fatigue than people with depression or a low level of happiness.…”
Section: Discussionsupporting
confidence: 91%
“…We were not able to determine whether the benefits of mood check-ins come from individuals consciously deciding to meditate based on their mood or if this effect occurs on a subconscious level. If occurring subconsciously, the meditation behavior may be a byproduct of improvements in mental health that are associated with better health behaviors [ 21 - 23 ]. Alternatively, mood check-ins may increase the perceived benefit of meditation, and thus increase performance of the behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect of well-being is life satisfaction. Research in the past years has made considerable progress in identifying the factors that influence people's subjective well-being all around the world (Diener et al, 1985;Kuppens et al, 2008;Kushlev et al, 2020). Scholars have distinguished two components of well-being: cognitive one related to the evaluation of the satisfaction with one's life as a whole, and an affective judgement that refers to positive and negative emotionality (Kuppens et al, 2008), which is going to be examined in this research, as we intend to examine the relationship of positive and negative affect, and life satisfaction.…”
Section: Correlates Of Positive and Negative Affects: Self-esteem Life Satisfaction And Vitalitymentioning
confidence: 99%